New paleoecological inferences based on the Early Pleistocene amphibian and reptile assemblage from Dmanisi (Georgia, Lesser Caucasus). Issue 162 (January 2022) - Blain, Hugues-Alexandre; Fagoaga, Ana; Sánchez-Bandera, Christian; Ruiz-Sánchez, Francisco J.; Sindaco, Roberto; Delfino, Massimo
Abstract: Dmanisi (Georgia) is one of the oldest Early Paleolithic sites discovered out of Africa. In addition, it is the best site to understand the first Homo deme out of Africa and the first hominin occupation of Central to Western Eurasia. It has produced more than 40 hominin remains, including several very informative skulls, found in direct association with faunal remains and numerous lithic artifacts. To date, fossil amphibians and reptiles are one of the few proxies that have been used to propose quantitative climate reconstructions for the time where the hominins were living at Dmanisi. The aim of the present study is to review and amplify the previous paleoclimatic interpretation given by Blain et al. (2014), with an enhanced methodology using geographic information system and based on uncertain distribution area-occupied distribution area discrimination technique. This procedure permits to approach to a more precise common species distribution area and then using the WorldClim v. 2.1 climate database to propose for the first time monthly reconstructions for temperature and rainfall, in addition to annual parameters. The same technique is used to infer dominant ecoregions through the study area and potential tree coverage. Dmanisi climate is newly reconstructed as warm and semi-arid, similar to the present-day Mediterranean climate. New estimates however suggest warmer temperatures than previously reconstructed, together with a slightly higher but much more irregular amount of rainfall. The aridity indexes suggest a six months dry period, from May to October. Associated regional paleoenvironment is mainly characterized by Mediterranean forests, woodlands, and scrub, and the potential tree coverage is around 25%, that is, much less forested than today. New estimates agree with the 'Iberian' hominin ecological model, and with other proxies (large mammals, small mammals and archaeobotanical remains) that indicate a period of increased aridity contemporaneous with human occupations of the site. Highlights: Dmanisi is one of the oldest Early Paleolithic sites discovered out of Africa. Climate is newly reconstructed as Mediterranean warm and semi-arid. New estimates however suggest warmer temperatures than previously reconstructed. Paleoenvironment is characterized by Mediterranean forests, woodlands, and scrub. Mediterranean biome was a suitable place for early hominins as early as 1.8 Ma.